Increasing Public Knowledge in Utilizing Waste as a Medium for Worm Cultivation - Santi Purnamasari; Marisa Elsera (PT FORMOSA CENDEKIA GLOBAL, 2022)
This community service program was carried out in Resun Village, North Lingga District, Lingga Regency. Some of the main problems that are a problem in Resun Village are the not yet optimal handling from Resun Village and the government to deal with waste problems faced by the people of Resun Village. Communities often throw garbage carelessly in rivers and in community forests that have not optimized the knowledge and importance of waste to be used and become a medium for a beneficial cultivation and create an environment free of waste and create a healthy environment. The results of this PKM activity can be described through the role of the community in carrying out a social action to create a healthy and waste-free environment. The process of increasing public knowledge in handling waste is carried out through 1 approach, namely: Socialization of waste utilization.